Is the ambit of judicial review in South Africa properly guarded to ensure that judges do not (ab)use it to the extent of replacing constitutional supremacy with judicial supremacy? - Malan, Koos (University of Pretoria, 2021)
Mini Dissertation (LLM (Constitutional and Administrative Law))--University of Pretoria, 2021.